ANALISIS DAMPAK GADGET TERHADAP PERILAKU SOSIAL ANAK SEKOLAH DASAR - Sapta Yuliansyah; Lishapsari Prihatini; Marleni, Marleni; Junior Zamrud Pahalmas (Nusantara Hasana Journal, 2025)
This study aims to examine the impact of gadgets on the social development of elementary school children, particularly fifth- and sixth-grade students at SDN 171 Palembang. The background of this research arises from the growing phenomenon of gadget ownership and usage among children. On the one hand, gadgets provide benefits such as enhancing creativity, communication skills, and access to information. On the other hand, they also bring negative effects such as decreased social interaction, tendencies toward individualism, and disciplinary issues. The research applied a descriptive qualitative method with data collection techniques including semi-structured interviews, participatory observation, and documentation involving students, parents, and homeroom teachers. The findings indicate that most students tend to use gadgets more for entertainment than for educational purposes. Regular and supervised gadget use still allows children to remain socially active, while excessive use leads to a decline in direct communication skills, social abilities, and self-control. Various internal, situational, social, and external factors influence how children use gadgets. The conclusion of this study highlights the importance of parental and teacher supervision and guidance to ensure that gadget usage remains limited in duration, directed toward positive purposes, and balanced with social interaction, so that children’s development can remain optimal.